2002
DOI: 10.1055/s-2002-23110
|View full text |Cite
|
Sign up to set email alerts
|

Diagnose und Therapie bei Stapesfrakturen und -luxationen

Abstract: The diagnosis of a stapes injury is despite the use of sophisticated technology, especially the CT-scan of the temporal bone, often very difficult. A sensitive anamnesis seems to be very important. It depends on the kind of injury which operative technique is to be applied in order to re-establish the ossicular chain. In our opinion, it is useful to take - if it is possible - the autolog stapes for the surgical re-establishment of transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In humans, they are indeed rarely fractured. ( 21 , 22 ) Occasionally the ossicles can be fractured without damage to the skull, for instance, if a sneeze is prevented; one unfortunate woman fractured a stapes during the effort of childbirth. ( 23 ) For auditory reasons, a desirable feature of the auditory ossicles is to be as stiff as possible with minimum mass.…”
Section: Some Bones Poorly Adapted To Resist Fracture: Auditory Ossicmentioning
confidence: 99%
“…In humans, they are indeed rarely fractured. ( 21 , 22 ) Occasionally the ossicles can be fractured without damage to the skull, for instance, if a sneeze is prevented; one unfortunate woman fractured a stapes during the effort of childbirth. ( 23 ) For auditory reasons, a desirable feature of the auditory ossicles is to be as stiff as possible with minimum mass.…”
Section: Some Bones Poorly Adapted To Resist Fracture: Auditory Ossicmentioning
confidence: 99%
“…3,4 However, the incidence of internal stapediovestibular dislocation without a stapes fracture is rare. Over the years, cases of stapediovestibular dislocation with intact stapes have been reported from all over the world, [5][6][7][8][9][10][11][12][13][14] as summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…5 If the patient still has some residual hearing, auditory chain reconstruction and tympanoplasty are usually performed. [6][7][8] Several methods and materials of reconstruction can be employed, such as the temporal myofascial flap or perichondrium, artificial auditory ostium, and autogenous columellar cartilage. 10…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] Direct trauma via external auditory canal with an ear hook is expected to be seen in the pediatric age group. Lasak et al, [6] reported 44 cases of middle ear injury through external auditory canal, but none had an avulsion injury.…”
Section: Discussionmentioning
confidence: 99%